Effect of Bacillus spp. on Lettuce Growth and Root Associated Bacterial Community in a Small-Scale Aquaponics System - Kasozi, Nasser; Kaiser, Horst; Wilhelmi, Brendan (Agronomy, 2021)
The integration of probiotics in aquaponics systems is a strategy for mitigating environmental impacts and for promoting sustainable agriculture. In order to understand the role of probiotics, we investigated the effect of a commercial probiotic mixture of Bacillus subtilis and B. licheniformis on the growth of lettuce (Lactuca sativa L.) under deep-water culture integrated with Mozambique tilapia (Oreochromis mossambicus). We determined plant growth, water quality parameters, and leaf mineral analysis, and assessed the influence of a probiotic mixture on the microbiota. Bacterial communities were analyzed by high-throughput 16S rRNA gene sequencing. Compared to the control systems, the addition of the probiotic Bacillus significantly increased the concentration of nitrate and phosphate in deep water culture solution, which contributed to improved lettuce growth. In both the growth trials, the Fv/Fm, the mean shoot dry weight, and the mean fresh weight of the harvested shoots from the Bacillus treatment were significantly higher than those observed for the control plants. Higher concentrations of phosphorus, potassium, and zinc in the lettuce leaves were found in systems that received the Bacillus. Although differences were observed at the phylum level, Proteobacteria and Bacteroidetes were predominant in both the Bacillus-treatment and the control systems. At the genus level, however, the communities present in the two types of systems were heterogeneous with Bacillus-treated systems, containing significantly higher numbers of Chryseobacterium, Bacillus, Nitrospira, Polynucleobacter, and Thermomonas. The results indicate that Bacillus supplementation can effectively alleviate nutrient deficiencies, improve water quality, and modify the composition of bacterial communities in aquaponics systems.
Keywords: aquaponics; lettuce; plant growth; probiotics; Mozambique tilapia